2021
DOI: 10.1159/000512791
|View full text |Cite
|
Sign up to set email alerts
|

Training Psychiatry Residents in Descriptive Psychopathology: A Systematic Review

Abstract: Purpose: Descriptive psychopathology (DP, sometimes called psychopathology or phenomenology) is the language of psychiatry and is dedicated to the description of mental symptoms. Due to its importance, there is an ongoing case to put it back at the heart of psychiatry and its training. This study seeks to examine the literature on how to train psychiatry residents in DP, including reported educational interventions and educational methods. Method: The authors conducted a systematic review following the PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…As pointed out by Jaspers and Parnas [7,8,13], training in DP should encompass both a knowledge framework and the clinical capacity to use it properly with a variety of patients and within increasingly complex healthcare systems. In this regard, a recent systematic review of the literature on how to train psychiatry residents in DP identified a series of shortcomings and challenges [14].…”
Section: Hot Topics For the Present And Future Of Dp Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…As pointed out by Jaspers and Parnas [7,8,13], training in DP should encompass both a knowledge framework and the clinical capacity to use it properly with a variety of patients and within increasingly complex healthcare systems. In this regard, a recent systematic review of the literature on how to train psychiatry residents in DP identified a series of shortcomings and challenges [14].…”
Section: Hot Topics For the Present And Future Of Dp Trainingmentioning
confidence: 99%
“…The current lack of clinical training and assessment in DP is a cause for major concern, as DP comes alive in the patient-psychiatrist dialogue [14]. Clinical practice within real work contexts with actual patients is essential, especially as DP is senseless without real patients and simulation has intrinsic limitations regarding essential aspects (e.g., empathy) in the patient-psychiatrist dialogue that leads to symptom formation [15].…”
Section: Hot Topics For the Present And Future Of Dp Trainingmentioning
confidence: 99%
See 3 more Smart Citations